An analysis of differences in kellgren-lawrence scores between patients with knee osteoarthritis and class II obesity versus those without obesity - Ambarukmi, Fransiska; Kusumah, Djoni; Dewi, Herfani H (ACTA Medical Health Sciences, 2025)
Individuals with overweight or obesity are at a higher risk of developing knee osteoarthritis (OA) compared to those with a normal body mass index (BMI). This increased risk is attributed to metabolic effects and the excessive mechanical load on the joint, which escalates with weight gain. Previous studies have established a correlation between the higher BMI and increased severity of joint damage in patients with knee OA. This analytic, comparative study utilized cross-sectional design to investigate the difference in Kellgren-Lawrence (KL) Score between patients with and without obesity who have knee osteoarthritis (OA) The analysis was conducted using secondary data from medical records and knee X-rays at Cianjur General District Hospital during 2020. A total of 50 patients were included, with 25 patients in each group (OA with obesity and OA without obesity). The majority of participants were female (80%), aged 56-65 years old (52%), and had a BMI classified as class II obesity (50%). KL Score ranged from grade 1 to 3. Data analysis using the non-parametric Mann- Whitney U test revealed a statistically significant difference in KL Score between the two groups (pvalue=0.000). The increased mechanical stress associated with obesity is hypothesized to be a causative agent that aggravates joint damage, as evidenced by the more severe degree of the Kellgren- Lawrence Score in the obese population. In conclusion, a significant difference in the severity of OA Genu degree, based on the Kellgren-Lawrence scoring system, was found between obese and non-obese patients. DOI : 10.35990/amhs.v4n1.p26-34 REFERENCES Kulkarni K, Karssiens T, Kumar V, Pandit H. Obesity and osteoarthritis. Maturitas [Internet]. 2016;89:22–8. Available from: http://dx.doi.org/10.1016/j.maturitas.2016.04.006 Kolasinski SL, Neogi T, Hochberg MC, Oatis C, Guyatt G, Block J, et al. 2019 American College of Rheumatology/Arthritis Foundation guideline for the management of osteoarthritis of the hand, hip, and knee. Arthritis Rheumatol. 2020;72(2):220–33. National Public Health Agenda. Osteoarthritis: 2020 update. 2020. Widjayanti Y. Gambaran keluhan akibat penurunan kadar hormon estrogen pada masa menopause. Adi Husada Nursing Journal [Internet]. 2016;2(1):96–101. Available from: https://adihusada.ac.id/jurnal/index.php/AHNJ/article/view/41/121 Loeser RF. Aging and osteoarthritis: the role of chondrocyte senescence and aging changes in the cartilage matrix. Osteoarthritis Cartilage [Internet]. 2009;17(8):971–9. Available from: http://dx.doi.org/10.1016/j.joca.2009.03.002 Dewi S, Kalim H, Alwi I. Rekomendasi IRA untuk diagnosis dan penatalaksanaan osteoartritis. Divisi Reumatologi Departemen Ilmu Penyakit Dalam FKUI/RSCM. 2014. p.1–3. Jameson J, Fauci A, Kasper D, Hauser S, Longo D, Loscalzo J. Harrison’s Principles of Internal Medicine. 20th ed. New York: McGraw Hill Education; 2018. Wharton S, Lau DCW, Vallis M, Sharma AM, Biertho L, Campbell-Scherer D, et al. Obesity in adults: a clinical practice guideline. CMAJ. 2020;192(31):E875–91. World Health Organization. Obesity and overweight. WHO; 2020. Zheng H, Chen C. Body mass index and risk of knee osteoarthritis: systematic review and meta-analysis of prospective studies. BMJ Open. 2015;5(12). Raud B, Gay C, Guiguet-Auclair C, Bonnin A, Gerbaud L, Pereira B, et al. Level of obesity is directly associated with the clinical and functional consequences of knee osteoarthritis. Sci Rep. 2020;10(1):1–7. Hardiyanti V, Devi M, Setiawan IMB, Wungou HPL. Correlation of body mass index and Kellgren-Lawrence degrees in genu osteoarthritis. Scr SCORE Sci Med J. 2020;2(1):1–5. Tiulpin A, Saarakkala S. Automatic grading of individual knee osteoarthritis features in plain radiographs using deep convolutional neural networks. arXiv. 2019;1–12. Kohn MD, Sassoon AA, Fernando ND. Classifications in brief: Kellgren–Lawrence classification of osteoarthritis. Clin Orthop Relat Res. 2016;474(8):1886–93. Mutiwara E, Najirman N, Afriwardi A. Hubungan indeks massa tubuh dengan derajat kerusakan sendi pada pasien osteoartritis lutut di RSUP Dr. M. Djamil Padang. J Kesehat Andalas. 2016;5(2):376–80. Widhiyanto L, Desnantyo AT, Djuari L, Kharismansha M. Correlation between knee osteoarthritis grade and body mass index in outpatients of Orthopaedic and Traumatology Department RSUD Dr. Soetomo. J Orthop Traumatol Surabaya. 2019;6(2):71. Reyfar K. Hubungan antara IMT dengan derajat keparahan radiologis Kellgren–Lawrence pada penderita OA lutut lansia di KPKM Reni Jaya Pamulang Tahun 2017. 2018. Ibrahim A, Alang AHM. Metodologi Penelitian [Internet]. Makassar: Gunadarma Ilmu; 2018. p.166. Available from: http://repositori.uin-alauddin.ac.id/12366/1/BUKUMETOLOGI.pdf Mulyatiningsih E. Terapan Riset. 2011. p.1–254. Reyes C, Leyland KM, Peat G, Cooper C, Arden NK, et al. Association between overweight and obesity and risk of clinically diagnosed knee, hip, and hand osteoarthritis: a population-based cohort study. Arthritis Rheumatol. 2016. Widhiyanto L, Desnantyo AT, Djuari L, Kharismansha M. Correlation between knee osteoarthritis grade and body mass index in outpatients of Orthopaedic and Traumatology Department RSUD Dr. Soetomo. J Orthop Traumatol Surabaya. 2014;2:2–31. Chu IJH, Lim AYT, Ng CLW. Effects of meaningful weight loss beyond symptomatic relief in adults with knee osteoarthritis and obesity: a systematic review and meta-analysis. Obes Rev. 2018;19(11):1597–607.